Sistem Pakar Penentuan Asesmen Keperawatan Kardiovaskular Menggunakan Metode Certainty Factor Berbasis Web - Ivan Ubaidillah Sekar Wibowo; Latifah Rifani; Wiwin Agus Kristiana; Aryo Nugroho (SMARTICS Journal, 2021)
Today's nurses are in charge of helping the performance of a doctor and interacting more directly with a patient. Patients who come to health facilities have different health problems, including those with the cardiovascular system. When there is a disturbance or blockage in the two parts of the body, it will interfere with blood circulation in the patient's body and cause a dangerous impact on the patient. However, it is not uncommon for a nurse to make mistakes in concluding a diagnosis due to a lack of focus. Therefore, one of the applications of technology in the world of health is applying artificial intelligence technology to help nurses determine the diagnosis accurately. With the Certainty Factor method, the nurse will determine the diagnosis based on subjective and objective data. The use of Forward Chaining algorithms to analyze thoughts and decide on this system will later predict whether a patient is diagnosed with a cardiovascular system. In addition, the use of the Laravel framework makes this system web-based, which is certainly easy to operate by all nursing personnel and is accurate in helping the diagnosis process to patients.